The Effect of Inflammatory Markers in Patients with Diabetes Mellitus - Al-Masaoodi, Rusul Ali (Technium BioChemMed, 2025)
The purposes of this research are to identify the significance of inflammatory substances in individuals with type 2 diabetes mellitus and investigate the relationship involving inflammatory responses and illness duration. The fifty specimens used in the present investigation were split between thirty specimens of individuals who had diabetes with type 2 and twenty specimens about the unaffected population. In this investigation, the body mass index (BMI), HbAIC, as well as levels of C-reactive proteins among individuals having diabetes type 2 and the unaffected population were calculated. also shows the relationship between HbAIC, CRP, and a body mass index HbA1C, CRRACTIVE PROTINE, and a body mass index all increased significantly (p<0.05) throughout the present study. Additionally, in individuals with diabetes with type 2, there was a substantial (p<0.05) positive association among the Creative Protein and body mass index (B and a significant (p<0.05) beneficial relationship among the C Reactive protein and HbA1C. According according to the research’s findings, those suffering from type 2 diabetes had higher levels of inflammation-related markers, and their HbAIC readings increased in tandem alongside the progression of the illness, suggesting an advantageous correlation across the two variables.